A Re-scaled Version of the Foster-Greer-Thorbecke Poverty Indices based on an Association with the Minkowski Distance Function - S. Subramanian (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This note advances a family of poverty measures, ??, which are derived as simple, normalized Minkowski distance functions. The ?? indices turn out to be the ?th roots of the corresponding Foster, Greer and Thorbecke P? indices. The re-calibration of P? terms of ?? could have certain possible advantages, which are reviewed in the note. While the ?? indices are not decomposable in the ordinarily understood sense of that term, they are amenable to the completely general decomposition procedure advanced by Shorrocks (?Decomposition Procedures for Distributional Analysis: A Unified Framework Based on the Shapley Value?) and discussed, here, as an application in the poverty context.
Keywords: 330; poverty measures; decomposition